2008
DOI: 10.1111/j.1365-3148.2007.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐based criteria for the care and selection of blood donors, with some comments on the relationship to blood supply, and emphasis on the management of donation‐induced iron depletion

Abstract: Blood Services, which, in the UK, spend over 0.5% of the NHS budget, are generally subject to quality, regulatory, economic and political authority. As only persons in good health should give blood, Services have refined donor selection criteria and aim to base them on evidence; but they also have to balance the number of donations collected with product demand. Applying selection criteria inevitably leads to deferrals, which donors experience very negatively. Compared with successful donors, even temporary de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 68 publications
1
62
0
Order By: Relevance
“…More subtle rewards include offers of free tests, such as those for high blood pressure, cholesterol, glucose etc, which are beyond the mandatory donation screening for hemoglobin concentration and infection markers. The arguments against encouraging these donations include inadvertent recruitment of individuals with a lifestyle that puts blood recipients at higher risk, but some providers feel unable to sustain a sufficient blood supply without such encouragement 30,31 . Pereira et al 32 showed that replacement donors present 2.5-fold higher seropositivity for HBV, HCV and HIV than volunteer donors.…”
Section: Conflict Of Interest Referencesmentioning
confidence: 99%
“…More subtle rewards include offers of free tests, such as those for high blood pressure, cholesterol, glucose etc, which are beyond the mandatory donation screening for hemoglobin concentration and infection markers. The arguments against encouraging these donations include inadvertent recruitment of individuals with a lifestyle that puts blood recipients at higher risk, but some providers feel unable to sustain a sufficient blood supply without such encouragement 30,31 . Pereira et al 32 showed that replacement donors present 2.5-fold higher seropositivity for HBV, HCV and HIV than volunteer donors.…”
Section: Conflict Of Interest Referencesmentioning
confidence: 99%
“…13 Thus, donors are a good population in which to evaluate novel tests of iron deficiency. In a population of healthy female blood donors we evaluated the diagnostic properties of hepcidin concentration as a test of iron deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, increasing the dataset size, resulted in lower UL scores, as shown in Figure 11d. This is because larger datasets contain combinations of diagnosis codes which appear in more records 3 . Thus, the anonymization of these datasets can be performed with lower information loss.…”
Section: Data Utility Evaluation Of Art U C (Fixed Utility Constraintmentioning
confidence: 99%
“…Healthcare data are essential for performing large-scale, low-cost analyses [18], which range from Genome-Wide Association Studies (GWAS) to predictive modeling [9,32] and have the potential to improve medical research and practice. For instance, the study in [14] used more than 350,000 records of the Scandinavian Donations and Transfusions database, along with the donors' and the recipients' health records, to answer whether blood transfusions transmit cancer, and it had a substantial impact on public health policies regarding restrictions placed on blood donors [3,13]. Another study [75] used an EHR database of over 300,000 records, to learn meaningful comorbidities, which are associated with different stages of Chronic Obstructive Pulmonary Disease (COPD).…”
Section: Introductionmentioning
confidence: 99%